Synthesis, Characterization, in vitro Antimicrobial Evaluation and in silico Molecular Docking and ADME Prediction of 4-Chlorophenyl Furfuran Derivatives bearing Pyrazole Moieties - Mathew, Manju; Chinnamanayakar, Raja; Ramanathan, Ezhilarasi Muthuvel (Asian Journal of Chemistry, 2020)
A series of 1-(5-(5-(4-chlorophenyl)furan-2-yl)-4,5-dihyropyrazol-1-yl ethanone (5a-h) was synthesized through E-(3-(5-(4-chloro-phenyl)furan-2-yl)-1-phenylprop-2-en-1-one (3a-h) with hydrazine monohydrate and sodium acetate. Totally, eight compounds were synthesized and their structures were elucidated by infrared, 1H & 13C NMR, elemental analysis, antimicrobial studies, in silico molecular docking studies and also in silico ADME prediction. Antimicrobial studies of the synthesized compounds showed good to moderate activity against the all the stains compared with standard drugs. in silico Molecular docking study was carried out using bacterial protein and BC protein. Synthesized compounds (5a-h) showed good docking score compared with ciprofloxacin. Antimicrobial study was carried out for 4-chlorophenyl furfuran pyrazole derivatives (5a-h). The results of assessment of toxicities, drug likeness and drug score profiles of compounds (5a-j) are promising.